Jovens e consumo midiático: os usos sociais das mídias dos jovens campo-grandenses - JOAO VICTOR VIEIRA REIS (2022)
The increasing use of electronic devices, including communication devices, has been one of the characteristics of the domestic environment since the second half of the 20th century. Young people born in the late 1990s grew up in a society marked by the social presence of the internet and digital technology in the media, which is why this generation is attributed greater familiarity and ease of use of the media. This work analyzes the relationship of young digital natives (Tapscott, 1999) with the media, exploring their social uses and how they integrate their daily practices. The research had a quantitative part and a qualitative stage, namely: 1,556 questionnaires were applied in schools and universities in Campo Grande in 2019, answered by young people aged between 16 and 18, and focus groups were held with 27 of these adolescents, in order to deepen the topics raised with the questionnaire. As a result, the research pointed to young people with diverse tastes and customs, with consumption guided by nostalgia and what is comfortable for them, but still ignorant of the potential of possible social uses with the media.